Parenting Stress and Maternal Emotional Difficulty: Predicting Children’s Attitudes and Anxiety about the COVID-19 Pandemic during lockdown - Samavati, Mona (Shahroud Journal of Medical Sciences, 2024)
Background: Due to the destructive effects of the COVID-19 pandemic and social crises, the present study aimed to investigate the role of parental stress and maternal emotions' difficulty in predicting children's attitudes and anxiety about the COVID-19 pandemic during lockdown. Methods: This research aimed to conduct an applied study with a descriptive-correlational data collection approach. The target population comprised all female and male students in public preschool and primary schools in Kermanshah city during the academic year 2020-2021. A total of 150 samples through the convenience sampling method completed the Parental Stress Index—Short Form (PSI-SF), The Difficulties in Emotion Regulation Scale (DERS), The Knowledge and Attitude Scale toward COVID-19 Pandemic, and Spence Children’s Anxiety Scale – Child (SCAS-Child). Statistical computations were performed using SPSS-22 software. The significant level was set at 0.05. Results: The results of the Pearson correlation test showed that there was a significant positive relationship between the parent's distress component and the child's anxiety level due to COVID-19 disease (Pvalue<0.01; r=0.23). Additionally, there was a significant positive relationship between the Children in difficulty component and children's anxiety levels due to COVID-19 disease (Pvalue<0.01; r=0.48). In addition, there was a significant positive relationship between the dysfunctional parent-child interaction component and children's anxiety about COVID-19 disease (Pvalue<0.01; r=0.48). There was a significant positive relationship between parental stress and child anxiety due to COVID-19 disease (Pvalue<0.01; r=0.48). Conclusions: According to the results of the present study, one of the important measures to maintain the mental health of children in critical situations is to educate parents, especially mothers, about controlling and regulating their own negative emotions. Complications due to their age and cognitive development should be presented to them.